L’image linguistique du Juif déjouée par les pragmatèmes. Le cas du discours antisémite et antisioniste - Pirogowska, Ewa (Neophilologica, 2020)
The concept of pragmateme as witnessed in various discursive settings is analyzed. It is demonstrated to be dependent on a diaphasic variant at work — it can be felicitously applied to utterances whose value hinges on the communicative context, and it proves inherent to the speech production of a given individual. Likewise, its value may depend on communicative circumstances and might be specific to a given speech community. Convenient examples are provided by the anti-Semitic and anti-Zionist discourses of the acclaimed French performer Dieudonné fanciers. Pragmateme’s instance taken into consideration relies on a single phonetic shape \ʃ ɔ.a.na.nɑ likely to correspond to two different spellings [chaud ananas] [Shoah nana]. It misrepresents the figure of a Jew, whose depreciating image tightens the ties between community members, where antiSemitism is perceived as an overarching value.